Exploring the landscape of student representation in medical curriculum development across U.S. MD schools: A comparative analysis - Ish Sethi; C. Jessica Dine (BMC Medical Education)
Abstract Background This study aimed to investigate the various models of student representation in curriculum development across medical schools in the United States, based on the participatory governance theory. Recognizing the critical role of student feedback in enhancing medical education, the work sought to assess the diversity of student representation models, identify key elements that contribute to effective student involvement, and evaluate the potential impact on curriculum outcomes. Methods An initial list of 166 allopathic MD schools was curated from the AAMC Medical Schools Admission Requirements website. Schools were selected based on the presence of information about student representation in curriculum design. This selection was refined through a Google search using specific search terms related to student representation, followed by an evaluation based on the amount and relevance of available information on each school’s website. The methodology involved a detailed examination of the websites for selected schools, focusing on the structure and organization of student involvement in curriculum development. Results Of the initial 166 medical schools, 49 (29.7%) had publicly available information on student involvement in curriculum development. These schools were categorized into three main models of student representation: direct representation, feedback-driven, and hybrid models. The analysis revealed significant diversity in how student representation is implemented, with each model exhibiting unique strengths and limitations. Direct representation models were found to facilitate substantive student roles in decision-making, feedback-driven models excelled in rapidly integrating student feedback into curricular adjustments, and hybrid models combined aspects of both to provide a comprehensive approach to student involvement. Conclusions There is no one-size-fits-all model for student representation in medical education. However, the hybrid model shows promise for its balanced approach to integrating student perspectives into curriculum development. Continuous evaluation and refinement of student representation models are essential for ensuring that medical education remains responsive to the needs of students and the evolving landscape of the medical field. This work underscores the importance of student feedback in medical education and advocates for further studies to quantify the impact of different models of student representation on educational outcomes and professional success.